Circulating CD30+CD4+ T Cells Increase Before Human Immunodeficiency Virus Rebound After Analytical Antiretroviral Treatment Interruption. (2nd November 2019) - Prator, Cecilia A; Thanh, Cassandra; Kumar, Shreya; Pan, Tony; Peluso, Michael J; Bosch, Ronald; Jones, Norman; Milush, Jeffrey M; Bakkour, Sonia; Stone, Mars; Busch, Michael P; Deeks, Steven G; et al.
Abstract: Background: Identification of nonviral markers of human immunodeficiency virus (HIV) infection that increase before viral rebound during analytical treatment interruption (ATI) may affect HIV persistence research. We previously showed that HIV ribonucleic acid (RNA) is enriched in CD30 + CD4 + T cells in many individuals. Here, we studied CD30 + CD4 + T-cell dynamics before ATI, during ATI (before detectable plasma RNA), and after HIV rebound. Methods: Peripheral blood mononuclear cells from 23 participants collected longitudinally from 5 Adult AIDS Clinical Trials Group studies incorporating ATI were included in this study. Flow cytometric characterization of expression of CD30 and markers of T-cell activation and exhaustion were performed along with HIV-1 RNA and deoxyribonucleic acid quantification and measurement of soluble plasma CD30 and CD30 ligand. Results: The percentage of CD4 + T cells expressing CD30 significantly increased from pre-ATI to postinterruption time points before detectible viremia (1.65 mean relative increase, P = .005). Seventy-seven percent of participants experienced an increase in CD30 + cells before viral rebound. In contrast, there were no significant differences between pre-ATI and postinterruption pre-rebound time points in percentages of lymphocytes expressing CD69, CD38/HLA-DR, or PD-1 until after HIV recrudescence. Conclusions: CD30 may be a surrogate marker of early replication or viral transcriptional activity before detection by routine peripheral blood sampling. Abstract : CD30 may be a surrogate marker of early replication or viral transcriptional activity before detection by routine peripheral blood sampling during analytical treatment interruption in people with HIV.